GERAKAN LITERASI SEKOLAH DALAM MENUMBUHKAN MINATBACA PADA PEMBELAJARAN DI SEKOLAH DASAR NEGERI MEMPAWAH HILIR - Nurhayati, Nurhayati; Asrori, Asrori; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this research is to determine theÂ  literacy movement SekolahDasar Negeri 1 Mempawah Hilir (the stages arein habituation, development, and learning) through reading interest in Sekolah Dasar Negeri 1 Mempwah Hilir 1 in terms of the aspects of literacy planning, literacy implementation, and literacy evaluation. The research was carried out at SekolahDasar Negeri 1 Mempawah Hilir. This research is a descriptive study with a qualitative approach. The subjects in this research were principals, teachers, and students while the data collection was done through observation, interviews, and documentation. The data analysis is done through stages: data reduction, data display, and conclusion drawing. Techniques for checking the validity of data using triangulation. The results of this research showed that literacy (habituation, teaching, and learning) through reading interest in the planning, implementation, supporting factors, inhibiting and evaluation stages of learning already done it. The character planningon learning by incorporating elements of literacy and designing the implementation of learning. The implementation of learning is done by the teacher with applying school literacy and reading interest that is carried out through literacy, teachers and is carried out every day by all school residents. The evaluation of learning is assessment of the process and assessment of learning outcomes.Keywords :literacy, reading interest, learning